Electrospun core-shell fibers for controlled oral delivery of hydrophilic drugs - Ee, Debbie Gek Hui (2017)
Oral delivery of hydrophilic drugs are challenging due to their limited bioavailability but is widely accepted, non invasive and easy to administer compared to traditional invasive injections as an administration route. One way of achieving controlled release of hydrophilic drugs is using core shell electrospun fibers made using coaxial electrospinning in a onestep single setup. In this project, dissolution mechanism of anionic eudragit fibers in vitro, optimization of electrospinning of PVA/eudragit core shell fibers and drug release using a hydrophilic mode drug FITC-dextran was investigated. Monolithic S100, L100 and S/L blends of eudragit fibers were successfully electrospun. SEM and mass change was used to characterize the dissolution of monolithic shell fibers with blends of S100 and L100 showing promise of achieving controlled drug release. Coaxial electrospinning was successfully used to electrospin core shell fibers and drug release results show that core shell fibers with a 95S:5L shell was able to achieve zero order release while 75S:25L showed a first order drug release over a 5 hour release period. The potential to achieve constant drug release is enormous however loading needs to be enhanced which can be achieved with greater optimization of electrospinning parameters.